(untitled) (Karya Ilmiah Mahasiswa (KIMA), 2024)
This research aims to find out the students’ perceptions of digital ethics in learning activities in the Learning Management System Kalam UMI and the difficulties that students find in doing activities in LMS Kalam UMI. The use of features in the Learning Management System Kalam UMI has been widely used in the online learning process at UMI. This research used a qualitative approach with a descriptive analysis method. This method was used by the researcher to describe and analyze the digital ethics literacy of students at UMI. The result of this research showed from one of the questionnaire items that 11 (64,7%) respondents chose Very Capable and one (5,9%) of them is seemingly Very Capable while 3 (17,6%) respondents chose Capable that indicates practicing ethics in social media use is still accepted. The researcher interviewed some of the respondents and found out that the role of ethics in carrying out activities on LMS Kalam UMI is very important. It can also be concluded that student perceptions of digital ethics in learning activities in the Learning Management System Kalam UMI are positive. This is shown by the large number of research respondents who perceive practicing ethics during learning activities on Kalam UMI, more than half of the research sample interviewed positively considered practicing ethics as important with numerous reasons and points of view.